Adalimumab in patients with hand osteoarthritis refractory to analgesics and NSAIDs: a randomised, multicentre, double-blind, placebo-controlled trial. Issue 9 (9th May 2014) - Chevalier, X; Ravaud, P; Maheu, E; Baron, G; Rialland, A; Vergnaud, P; Roux, C; Maugars, Y; Mulleman, D; Lukas, C; Wendling, D; Lafforgue, P; et al.
Abstract : Aim: To test the efficiency of tumour necrosis factor blockers (adalimumab) in patients with painful refractory (non-responders to analgesics and non-steroidal anti-inflammatory drugs (NSAIDs)) hand osteoarthritis (OA). Methods: We performed a randomised, double-blind, placebo-controlled, parallel group, multicentre study. Patients were randomised to: 1/1 adalimumab 40 mg for two subcutaneous injections at a 15-day interval or placebo and monitored for 6 months. The primary outcome was the percentage of patients with an improvement of more than 50% in global pain (Visual Analogue Scale) between week 0 (W0) and week 6 (W6). Secondary outcomes included the number of painful joints, swollen joints, morning stiffness duration, patient and practitioner global assessments, functional indexes for hand OA, and consumption of analgesics. Analysis on the mean primary outcome measure was done on patients who received at least one injection. Results: 99 patients were recruited and 85 patients were randomised. Among them, 37 patients in the placebo group and 41 in the adalimumab group received at least one injection and were evaluated at W6 (n=78) on the main efficacy outcome. Mean age was 62 years, 85% were women, and mean level of pain was 62 mm at W0. At W6, 35.1% in the adalimumab group versus 27.3% in the placebo group had a pain reduction ≥50% (RR 1.12 (95% CI 0.82 to 1.54; p=0.48). There were no statistical differences for all secondary end points. The rate of adverse events was similar in the two groups. Conclusions: Adalimumab was not superior to placebo to alleviate pain in patients with hand OA not responding to analgesics and NSAIDs. Trials registration number: NCT00597623.